Assessing suitability of water for irrigation in Bulgaria - Dimitrov, Peter; Kalcheva, Spaska; Simeonova, Tsetska; Kathijotes, Nicholas (My University, 2008)
The drying up, the intensive usage of near future almost all water reserves of good quality in lots of regions in Bulgaria and their irregular distribution on the country area, has shown that the part of the available set up irrigated area should use water of poorer quality. Quality control on the water for irrigation is needed to avoid emerging problems as decreasing the yield of agriculture and worsening its quality at using inadequate quality water.The development of a assessing system for the suitability of the water for irrigation aims to protect cultivated crops at using lower quality irrigation water. The system use laboratory analysis information, cultivated crops data, soil and agro-climatic characteristics, irrigation technology, legal rules and some additional parameters. The paper presented the main directions for determination of applicability of irrigation water at various crops on the basis of the assessment of its quality, exactly - the construction of irrigation water quality indicators database and assessment of the irrigation water quality, focusing on the methodology for decision-making for applicability of irrigation water at various crops and on the recommendations’ elaboration for irrigation water considering qualitative parameters of the available water. The database includes permanent information about the impact of the irrigation water quality on the agricultural production, personal information about water users, data about the water sources and its water samples, water indicators from laboratory analysis.

The drying up, the intensive usage of near future almost all water reserves of good quality in lots of regions in Bulgaria and their irregular distribution on the country area, has shown that the part of the available set up irrigated area should use water of poorer quality. Quality control on the water for irrigation is needed to avoid emerging problems as decreasing the yield of agriculture and worsening its quality at using inadequate quality water.The development of a assessing system for the suitability of the water for irrigation aims to protect cultivated crops at using lower quality irrigation water. The system use laboratory analysis information, cultivated crops data, soil and agro-climatic characteristics, irrigation technology, legal rules and some additional parameters. The paper presented the main directions for determination of applicability of irrigation water at various crops on the basis of the assessment of its quality, exactly - the construction of irrigation water quality indicators database and assessment of the irrigation water quality, focusing on the methodology for decision-making for applicability of irrigation water at various crops and on the recommendations’ elaboration for irrigation water considering qualitative parameters of the available water. The database includes permanent information about the impact of the irrigation water quality on the agricultural production, personal information about water users, data about the water sources and its water samples, water indicators from laboratory analysis.
Keywords: Water quality assessment; Irrigation; Methodology; Assessing system; Database; Water quality assessment; Irrigation; Methodology; Assessing system; Database